Tracking a sample of patients lost to follow-up has a major impact on understanding determinants of survival in HIV-infected patients on antiretroviral therapy in Africa - Geng, Elvin H.; Glidden, David V.; Emenyonu, Nneka; Musinguzi, Nicolas; Bwana, Mwebwesa Bosco; Neilands, Torsten B.; Muyindike, Winnie; Yiannoutsos, Constantin T.; Deeks, Steven G.; Bangsberg, David R.; Martin, Jeffrey N. (Tropical Medicine & International Health, 2010)
Objective: To date, data regarding the determinants of mortality in HIV-infected patients starting antiretroviral therapy (ART) in Africa have been primarily derived from routine clinical care settings practicing the public health approach. Losses to follow-up, however, are high in these settings and may lead to bias in understanding the determinants of mortality. Methods: We evaluated HIV-infected adults initiating ART between January 1, 2004 and September 30th, 2007 in an ART clinic in southwestern Uganda. Clinical and demographic characteristics were obtained through routine clinical care. In evaluating determinants of mortality, a ‘naı ¨ve’ analysis used only deaths known through routine processes. A ‘sample-corrected’ approach incorporated, through probability weights, outcomes from a representative sample of patients lost to follow-up whose vital status was ascertained through tracking in the community. Results: In 3,628 patients followed for up to 3.75 years after ART initiation, the ‘naı ¨ve’ approach identiﬁed male sex and lower pre-ART CD4 count as independent determinants of mortality. The ‘sample-corrected’ approach found lower pre-ART CD4 count, older age, lower weight and calendar year of ART initiation, but not male sex, to be independent determinants of mortality. Conclusions: Analyses to identify determinants of mortality in HIV-infected patients on ART in Africa that do not account for losses to follow-up can identify spurious associations and miss actual relationships – both with the potential to mislead public health efforts. A sampling-based approach to account for losses to follow-up represents a feasible and potentially scalable method to strengthen the evidence available for implementation of ART delivery in Africa.
Keywords: Antiretroviral scale-up strategies; Losses to follow-up; Determinants of mortality on antiretroviral therapy; Sampling studies; Monitoring and evaluation; Africa